The Effect of Clearance on the Performance of Machine Husking Rubber Rolls for Two (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The effect of clearance between cylinders of  machine husking rubber rolls (type Yanmar rubber roll – ST 50) on rice husk quality and breakage percentage was evaluated for two cultivars of rice. Tarm Hashemi (TH) and Daillman (DM) and clearance between cylinders of machine husking rubber at three different levels of 0.4, 0.6 and 0.8mm.The experiment was done in factorial experiment under complete randomized design (CRD) with three replications the results indicate  that the TH cultivar is significantly better than the D M in all studied traits. There was a negative relationship between increased clearance with head rice percentage and brown rice percentage in addition to the positive relationship between the increased percentage of cracked grain ,broken rice percentage and husking efficiency.